Ecuador's Cantonal (Municipal) Planning System: The Need for Reform - Manuel Benabent-Fernández de Córdoba; Lorena Vivanco-Cruz (Íconos)
Local planning in Ecuador has undergone major changes as a result of the approval of the “Ley Orgánica de Ordenamiento Territorial, Uso y Gestión de Suelo” (Local Territorial Planning and Land Management Organic Law) and by the development of new planning instruments such as the “Land Use and Management Plan” and the “Territorial Development and Management Plan”. As a result, planning at the “cantonal” (municipal) level has become more complex and local administrations are having trouble in completing these documents. This article wants to figure out the causes of these difficulties and show that the current legislation is muddled by the uselessness of the required planning instruments and because of the mistaken conflation of short term development planning with long term territorial management. Following a close analysis of legislative texts and other written documents, the article reconstructs the evolution of Ecuadorian legislation and the process that shaped the current “cantonal” (municipal) planning system. The serious inconsistencies of the current legal framework are exposed and the problems it provokes are shown. This validates the need to reform the system in order to make it more workable and operational.